THE IMPORTANCE OF WORKS OF MUHAMMAD SHIBLI NOMANI - Bhat, Samee- Ullah (Journal of Islamic Studies and Humanities, 2018)
This article aims at describing and examining life and works of Muhammad Shibli Nomani. With a historical and content analysis, this paper draws several conclusions. First, the prominent scholar of the Indo-Pak subcontinent of the modern times earns global name and fame through his multiple contributions. These include an accomplished tremendous excellence in numerous walks of human knowledge, arts and science, language and literature, research and criticism, philosophy and scholasticism, history and biography. Secondly, in all his eminent writings, Shibli makes full utilization of primary sources. It is because of this full use of the primary sources that his writings are outstanding in nature not only for the wealth of knowledge but also for interpretation and presentation of facts collected from a number of sources. Third, Shibli’s historical writings were primarily written to refute the unfounded allegations of the European writers on Islam and Muslim rule, to acquaint the Muslims with their glorious past, and to draw them out of stagnancy and obscurantism. AbstrakArtikel ini bertujuan untuk mendeskripsikan dan meneliti kehidupan dan karya-karya Muhammad Shibli Nomani. Dengan menggunakan analisis sejarah dan konten, penelitian ini berhasil mendapatkan beberapa kesimpulan. Pertama, sang sejarahwan terkemuka dari Indo-Pakistan memperoleh nama besar dan kemasyhuran dari beberapa kontribusi yang dia berikan. Termasuk di antaranya, pencapaian yang mengagumkan dalam beragam bidang ilmu pengetahuan manusia, seni dan sains, bahasa dan sastra, penelitian dan kritisisme, dan sejarah dan biografi. Kedua, dalam semua karya tulisnya, Shibli memanfaatkan sumber-sumber utama. Penggunaan sumber-sumber utama inilah yang menjadikan tulisan-tulisan itu sangat mengagumkan bukan hanya karena kekayaan pengetahuan namun juga karena interpretasi dan penyajian fakta yang terkumpul dari beberapa sumber tersebut. Ketiga, karya tulis kesejarahan Shibli utamanya ditulis untuk membantah tuduhan tanpa dasar dari para penulis Eropa tentang Islam dan hukum Islam, untuk memperkenalkan orang-orang Muslim dengan masa lalu mereka yang mulia, dan untuk menarik mereka keluar dari kemandekan dan obskurantisme.